Antiinflammatory and Antioxidant Activity of Chlorophytum borivilianum Root Extracts - DEORE, S.L.; KHADABADI, S.S. (Asian Journal of Chemistry, 2010)
The aqueous, hydro alcoholic and methanolic extract of Chlorophytum borivilianum (liliaceae) roots were investigated for antiinflammatory and antioxidant activity. Antiinflammatory activity was studied by carragenan induced rat paw oedema model. Methanolic and aqueous extract shows most significant antiinflammatory activity as compared to hydro alcohloic extract. Same extracts were studied for antioxidant activity. The assay methods used were DPPH and nitric oxide method. In both free radicals induced assay methods, methanolic extract shows maximum activity as compared to aqueous and hydro-alcoholic extracts.